2011
DOI: 10.1007/s10681-011-0465-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genes Rpp2, Rpp4, and Rpp5 for resistance to soybean rust

Abstract: Asian rust, caused by the fungus Phakopsora pachyrhizi, is the most severe disease currently threatening soybean crops in Brazil. The development of resistant cultivars is a top priority. Genetic characterization of resistance genes is important for estimating the improvement when these genes are introduced into soybean plants and for planning breeding strategies against this disease. Here, we infected an F 2 population of 140 plants derived from a cross between 'An-76', a line carrying two resistance genes (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 31 publications
1
54
0
1
Order By: Relevance
“…Although this study primarily focused on the reactions for 16 differentials, of which 13 contained Rpp1-5 and their associated alleles, the preliminary results demonstrate that PI 567102B carrying Rpp6 (Li et al 2012) and the No6-12-1 line pyramided with Rpp2, Rpp4, and Rpp5 (Lemos et al 2011) produced a resistant reaction to some recent rust populations from the three South American countries (data not shown). and South America.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although this study primarily focused on the reactions for 16 differentials, of which 13 contained Rpp1-5 and their associated alleles, the preliminary results demonstrate that PI 567102B carrying Rpp6 (Li et al 2012) and the No6-12-1 line pyramided with Rpp2, Rpp4, and Rpp5 (Lemos et al 2011) produced a resistant reaction to some recent rust populations from the three South American countries (data not shown). and South America.…”
Section: Discussionmentioning
confidence: 96%
“…This work elucidates the pathogenicity of P. pachyrhizi populations from Argentina, Brazil, and Paraguay from the 2010/2011-2014/2015 seasons, and provides a dataset useful for comparing pathogenicity data obtained in the past and for the future monitoring of pathogen populations. In an on-going study, the pathogenicity of the P. pachyrhizi populations from the three countries has been evaluated using the differentials with Rpp1-5 and their additional alleles, PI 567102B carrying Rpp6 (Li et al 2012) and the No6-12-1 line pyramided with Rpp2, Rpp4, and Rpp5 (Lemos et al 2011). In the future, a more informative dataset containing infection types of the two new differentials would be useful in breeding programs to develop rust resistant cultivars for P. pachyrhizi populations outside of Argentina, Brazil, and Paraguay (e.g., Central America).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recessive allele rpp2 [? It was later confirmed to map to the same region in a population consisting of 140 F 2 plants derived from a cross between 'An76,' which carries Rpp2 and Rpp4, and 'Kinoshita,' carrying Rpp5 (Lemos et al 2011). The gene was localized to a 12.9-cM interval between the SSR markers Sat_255 and Satt620 on chromosome 16 using a population of 130 F 2:3 derived lines developed from a cross between 'BRS 184' and PI 230970 (Silva et al 2008).…”
mentioning
confidence: 90%
“…Varieties with two pyramided resistance genes tend to express greater durability of resistance than varieties with a single gene [73,74]. Lemos et al [75] and Yamanaka et al [76] reported that a variety with three resistance genes (Rpp2, Rpp4 and Rpp5) showed significantly higher resistance than its ancestor, showing that pyramiding strategy is effective to increase the rust resistance.…”
Section: Resistancementioning
confidence: 99%